Analysis of Students' Perceptions of Artificial Intelligence Utilization in Completing Academic Tasks - Rizqy, Muhammad; Fasya, Bayu Hadiatma; Jannah, Miftahul; Gunawan, Gunawan (Indonesian Journal of Teacher Education, 2025)
The use of Artificial Intelligence (AI) has become increasingly widespread in higher education, particularly in assisting students with academic assignments. This study aims to analyze students’ perceptions regarding the utilization of AI in completing academic tasks, including patterns of use, frequency of application, and the types of assignments that most commonly involve the technology. In addition, the study evaluates students’ views on the benefits of AI, such as improved understanding of course material, time efficiency, and enhanced quality of academic work. On the other hand, the survey also explores students’ concerns related to plagiarism, violations of academic ethics, and the potential dependence on technology. The method employed is a quantitative survey using questionnaires distributed to students from various study programs. The results are expected to provide a comprehensive overview of students’ attitudes and tendencies in employing AI and to serve as a basis for educational institutions in formulating policies for the wise and responsible use of AI in academic settings.